Implementasi Sistem Keamanan Rumah Berbasis Pengenalan Wajah untuk Peningkatan Keamanan Residensial - Rahmatunnisa, Elsa Nabila; Fernanda, Billy Adrian; Maulana, Yusuf; Aripin, Ali Maulana Hapid (Fakultas Teknik Universitas Hamzanwadi, 2024)
The objective of this research is to develop a home security system that utilizes facial recognition technology using the Haar Cascade method and ESP32CAM. In the face of criminal threats, the importance of an effective home security system is increasing. The facial recognition method employed in this study is the Haar Cascade method, which utilizes specific facial features to identify individual identities. The ESP32CAM sensor is used as a camera to capture facial images of the home occupants. The research involves the process of collecting facial image data from the home occupants, which is then used to train the facial recognition model. Subsequently, the model is implemented in a home security system that is connected to the internet and equipped with motion sensors. When motion is detected, the ESP32CAM camera captures an image of the visitor's face and compares it with the previously identified facial data. If a match is found, the system grants access to the visitor. The research results demonstrate that the developed home security system achieves accurate facial recognition with a high success rate. Therefore, this system has the potential to enhance home security and provide better protection for its occupants